Perancangan Inverter Satu Fasa 12V DC ke 220V AC Berbasis Ic PWM Tipe CD4047BE - Ferdiansyah, Riko; Ramadhan, Fajar Aditya; Hadiyansah; Filabda, Nadia Aden; Syamsuddiin, Achmad (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
An inverter is an electronic device that functions to convert direct current (DC) voltage into alternating current (AC) voltage. In this design, a single-phase inverter is developed to convert 12V DC into 220V AC using a PWM IC type CD4047BE as the pulse signal generator. The CD4047BE is operated in astable mode to produce a symmetrical square wave signal, which is then amplified and used to control power transistors or MOSFETs that act as switching devices for the step-up transformer. The transformer increases the output voltage up to 220V AC. This system is designed for small-scale applications such as emergency lighting or light electronic devices. Testing showed that the inverter circuit is capable of generating AC voltage with a frequency close to 50 Hz and a waveform that approximates a square wave. These results indicate that the CD4047BE is effective as a PWM controller in a simple inverter system.